The relation between finger gnosis and mathematical ability: why redeployment of neural circuits best explains the finding - Penner-Wilger, Marcie; Anderson, Michael L. (Frontiers in Psychology, 2013)
This paper elaborates a novel hypothesis regarding the observed predictive relation between finger gnosis and mathematical ability. In brief, we suggest that these two cognitive phenomena have overlapping neural substrates, as the result of the re-use (“redeployment”) of part of the finger gnosis circuit for the purpose of representing numbers. We offer some background on the relation and current explanations for it; an outline of our alternate hypothesis; some evidence supporting redeployment over current views; and a plan for further research.